Individuality In the Educational Philosophy of Allama Muhammad Iqbal - Imam Bahroni (At-Ta'dib, 2011)
Nowadays, Muslim Ummah all over the world likely at the cross road,at the position where they watch clearly a phenomenon of life that directsthem into surprising modern civilization with full creativities and innovations,but far away from the true values of Islamic education. On the other hand,they observe vividly numerous dimensions of life that direct every individualinto strong morality, norms and right way of life to discover the Ultimate Reality.This social fact at the end compelled every one of modern people to selectwhich one among these two is the correct ideal for the truth of life.This article tries to elaborate the concept of individuality in the educationalphilosophy of Allama Muhammad Iqbal 2 . In his Lectures, Iqbal elaborated thatindividuality is not a datum but an achievement. It is the fruit of a constant,strenuous effort in and against the forces of the external environment as well asthe disruptive tendencies within man himself. The life of individuality (the Ego),he further explained is a kind of tension caused by the Ego invading theenvironment and the environment invading the Ego.An individual is the basis of all aspects of educations, which then mustbe educated and concerned together with the development of its relationshipto the community. Like the philosopher, the educator must necessarily inquireinto the nature of these two terms of his active individual and the environment,which ultimately determine the solution of all his problems.